PEMBERDAYAAN GABUNGAN KELOMPOK TANI DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI PETANI - Dewi Maryam; Shonhaji Shonhaji; Fauzi Fauzi; Lutfi Zaimuddin; Tontowi Jauhari (Fakultas Pertanian, Universitas Janabadra, 2023)
Empowerment in the field of agriculture is one of the important sectors in Indonesia's development efforts to combat poverty. According to the regulations of the Ministry of Agriculture, farmers are organized and structured within farmer groups in each hamlet and farmer group cooperatives (Gapoktan) at the village level. This study aims to obtain a deep understanding of the empowerment activities in the